Analisis Kebutuhan Pedagang Kaki Lima Atas Keputusan Relokasi sebagai Wujud Implementasi Kebijakan Peraturan Tata Tertib Kota Tahun 2016-2017 (Survey di Kota Ponorogo) - Dhika Amalia Kurniawan (University of Darussalam Gontor, 2017)
City is one of assets possessed by a region, so its comfort, beauty and order must be preserved for the purposes and prosperity together. But the problem often arises is the emergence of the impact that resulted in the security and beauty city as well as the area becomes disturbed is the problem of street hawkers (street vendors). Where the street vendors have been using the means of public facilities in the city, in this case is the city of Ponorogo. Along the highway Ponorogo decorated by the street vendors who sell from the morning and change with street vendors who sell afternoon untilnight. Not only the beauty of the city is threatened, congestion has become common place in Ponorogo, besides causing scattered rubbish everywhere as well as improperly buyer motorcycle parking adds to the noise of the Ponorogo city. This research uses descriptive qualitative method by doing interview, observation and documentation. The results of this study concluded that the street vendors who will be relocated are only street vendors located on Ponorogo city protocol road. They are willing to relocate in the hope that local governments provide more than ever before welfare benefits such asproviding new business ventures and strategic new places, crowded and announced as a culinary tourism center, security guarantees, safeguards and other expectations. The street vendors hope in a new place their trade business can be balanced even can grow, not decreased in terms of income.